2015
DOI: 10.5958/2394-2754.2015.00030.2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Early versus Conventional delay in Postoperative oral intake in Women undergoing Cesarean Section under regional anaesthesia

Abstract: The rate of cesarean delivery is increasing around the world. A traditional graduated dietary regimen, "nothing by mouth" for 24 hours, or until the presence of bowel sounds or passing flatus is still practised after cesarean delivery. In recent studies, an early oral intake has been recommended instead of the traditional dietary regimen for women after cesarean delivery. Our study aims at comparing the safety and efficacy of early versus conventional post-operative oral intake in patients undergoing caesarean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…In our study, time for return to regular diet was statistically significant shorter among group A (P value 0.0001). The same was reported by LR, 2017, and Devi et al, 2015 with different mean time to return to regular diet in each study and this may be due to the different approaches of feeding we used [20,21] .…”
Section: Discussionsupporting
confidence: 71%
“…In our study, time for return to regular diet was statistically significant shorter among group A (P value 0.0001). The same was reported by LR, 2017, and Devi et al, 2015 with different mean time to return to regular diet in each study and this may be due to the different approaches of feeding we used [20,21] .…”
Section: Discussionsupporting
confidence: 71%
“…24 Devi et al found in another study that women in the early feeding group had significantly shorter time interval to first noticed bowel movement after surgery of 6.97 ± 0.71 hours compared with the conventionally fed women with 14.96 ± 4.97 hours. 4…”
Section: Discussionmentioning
confidence: 99%
“…According to Devi et al, a graduated traditional dietary schedule, "nothing by mouth" for 24 hours, or till the return of bowel sounds or the patient passes flatus is still being practiced after C-section. 4 Recently, there have been recommendations in favor of early oral intake rather than the traditional delayed oral intake after cesarean delivery. 5,6 There have been concerns regarding the effects of early oral intake on postoperative ileus plus other complications after cesarean delivery.…”
Section: Introductionmentioning
confidence: 99%